Thermally activated delayed fluorescence (TADF) emitters: sensing and boosting spin-flipping by aggregation - Mazumdar, Ashish Kumar; Nanda, Gyana Prakash; Yadav, Nisha; Deori, Upasana; Acharyya, Upasha; Sk, Bahadur; Rajamalli, Pachaiyappan (Beilstein Journal of Organic Chemistry, 2022)
Metal-free organic emitters with thermally activated delayed fluorescence (TADF) characteristics are emerging due to the potential applications in optoelectronic devices, time-resolved luminescence imaging, and solid-phase sensing. Herein, we synthesized two (4-bromobenzoyl)pyridine (BPy)-based donor–acceptor (D–A) compounds with varying donor size and strength: the emitter BPy-pTC with tert-butylcarbazole (TC) as the donor and BPy-p3C with bulky tricarbazole (3C) as the donor unit. Both BPy-pTC and BPy-p3C exhibited prominent emission with TADF properties in solution and in the solid phase. The stronger excited-state charge transfer was obtained for BPy-p3C due to the bulkier donor, leading to a more twisted D–A geometry than that of BPy-pTC. Hence, BPy-p3C exhibited aggregation-induced enhanced emission (AIEE) in a THF/water mixture. Interestingly, the singlet–triplet energy gap (ΔEST) was reduced for both compounds in the aggregated state as compared to toluene solution. Consequently, a faster reverse intersystem crossing rate (kRISC) was obtained in the aggregated state, facilitating photon upconversion, leading to enhanced delayed fluorescence. Further, the lone-pair electrons of the pyridinyl nitrogen atom were found to be sensitive to acidic protons. Hence, the exposure to acid and base vapors using trifluoroacetic acid (TFA) and triethylamine (TEA) led to solid-phase fluorescence switching with fatigue resistance. The current study demonstrates the role of the donor strength and size in tuning ΔEST in the aggregated state as well as the relevance for fluorescence-based acid–base sensing.
Keywords: intramolecular charge transfer; molecular aggregates; sensing; thermally activated delayed fluorescence (TADF)